2015
DOI: 10.3727/096368915x686931
|View full text |Cite
|
Sign up to set email alerts
|

Current Proceedings of Cerebral Palsy

Abstract: Cerebral palsy (CP) is a complicated disease with varying causes and outcomes. It has created significant burden to both affected families and societies, not to mention the quality of life of the patients themselves. There is no cure for the disease; therefore, development of effective therapeutic strategies is in great demand. Recent advances in regenerative medicine suggest that the transplantation of stem cells, including embryonic stem cells, neural stem cells, bone marrow mesenchymal stem cells, induced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 184 publications
(198 reference statements)
0
26
0
1
Order By: Relevance
“…Epidemiological studies have found that the global prevalence of CP is 1.5-4 per 1000 live births, and the prevalence is higher in poor areas [3,4]. For example, with a prevalence of 3.6 per 1000 newborns in the United States, more than one hundred thousand children are affected in this country alone [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have found that the global prevalence of CP is 1.5-4 per 1000 live births, and the prevalence is higher in poor areas [3,4]. For example, with a prevalence of 3.6 per 1000 newborns in the United States, more than one hundred thousand children are affected in this country alone [5].…”
Section: Introductionmentioning
confidence: 99%
“…Current treatments include pharmacological interventions, surgical interventions, physical and behavioral therapy, mechanical aids, and management of associated medical conditions. Although these commonly used clinical treatments of CP are multitudinous, none have accomplished a satisfying curative effect [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Thymus derived T-cells (myelin reactive) migrate to the blood brain barrier and stimulate an inflammatory cascade in the CNS [3]. …”
Section: Introductionmentioning
confidence: 99%
“…1 Se entiende el concepto de PC como un desorden neurológico, con una presentación heterogénea, al igual que sus posibles causas 2 ; en la mayoría de los casos desconocidas pero con un amplio rango de factores asociados, como la asfixia perinatal, bajo APGAR al nacer, bajo peso 3 , género masculino, embarazo múltiple, infecciones intrauterinas, recién nacidos pre-términos. 4,5 (ver tabla 1. Factores asociados, rx).…”
Section: Introductionunclassified